STRUCTURAL PERFORMANCE EVALUATION OF RCC STRUCTURE WITH SHEAR WALL BY USING ETABS SOFTWARE - Prof. Vikas P. Jadhao; Abhijeet Shrikant Jagalpurkar; Rohit Datta Kusumkar; Yash Anna More; Jayesh Suresh Patil; Pranoti Nilkanth Sonar (International Educational Journal of Science and Engineering, 2025)
This study examines how buildings behave during earthquakes using equivalent Static method of analysis. Buildings with shear walls are now more common in earthquake-prone areas because they provide better resistance compared to buildings without shear walls. The main objective of this study is to find the best location for shear walls and evaluate their effectiveness in RCC buildings. For this analysis, G+5 RCC building considered under seismic zones II with appropriate load combinations as per IS 875 part (I to v). The structures are analyzed using ETABS software. The shear walls start from the foundation and continue throughout the entire building.